METTL3 regulates inflammatory pain by modulating m6A‐dependent pri‐miR‐365‐3p processing. Issue 1 (19th November 2019) - Zhang, Chenjing; Wang, Yin; Peng, Yunan; Xu, Hongjiao; Zhou, Xuelong
Abstract: N 6 ‐methyladenosine (m 6 A) modification in RNA has been implicated in diverse biological processes. However, very little is currently known about its role in nociceptive modulation. Here, we found that the level of spinal m 6 A modification was significantly increased in a mouse model of Complete Freund's Adjuvant (CFA)‐induced chronic inflammatory pain, which was accompanied with the augmentation of methyltransferase‐like 3 (METTL3) expression in the spinal cord. Knockdown of spinal METTL3 prevented and reversed CFA‐induced pain behaviors and spinal neuronal sensitization. In contrast, overexpression of spinal METTL3 produced pain behaviors and neuronal sensitization in naive mice. Moreover, we found that METTL3 positively modulated the pri‐miR‐65‐3p processing in a microprocessor protein DiGeorge critical region 8‐dependent manner. Collectively, our findings reveal an important role of METTL3‐mediated m 6 A modification in nociceptive sensitization and provide a novel perspective on m 6 A modification in the development of pathological pain.